2005
DOI: 10.1179/136485905x51517
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and field tests of the effectiveness of the lemon-eucalyptus extract, Citridiol, as a repellent against land leeches of the genusHaemadipsa(Haemadipsidae)

Abstract: Citridiol is an extract of the leaves of Corymbia citriodora (Myrtaceae), the lemon eucalyptus, and mostly consists of p-menthane-3,8-diol isomers. The effectiveness of this extract as a repellent against land leeches of the genus Haemadipsa (Haemadipsidae), primarily H. sylvestris, was tested in the laboratory and field, in Peninsular Malaysia. The formulation tested, Mosi-guard Natural spray, contained 40% (w/w) Citridiol in a base of ethanol, water and isopropanol. In the laboratory test, specimens of H. sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
0
4
0
3
Order By: Relevance
“…This property is partially due to its low volatility, which is different from that of natural repellent terpenoids. PMD was active against Aedes aegypti, Aedes albopictus, , Culex nigripalpus, Culex pipiens, Anopheles gambiae, ,, Ochlerotatus triseriatus, Ochlerotatus taeniorhynchus, Haemadipsa sylvestris, Haemadipsa picta, Stomoxys calcitrans, and nymphs of Ixodes ricinus, among others. Repellents exert their effects at a distance through olfactory sensitivities associated with mosquito antennae and maxillary palps. It has been reported how DEET, picaridin, IR3535, and PMD activated the odor receptor CquiOR136 of Culex quinquefasciatus, responsible for the detection and repellence …”
Section: Introductionmentioning
confidence: 99%
“…This property is partially due to its low volatility, which is different from that of natural repellent terpenoids. PMD was active against Aedes aegypti, Aedes albopictus, , Culex nigripalpus, Culex pipiens, Anopheles gambiae, ,, Ochlerotatus triseriatus, Ochlerotatus taeniorhynchus, Haemadipsa sylvestris, Haemadipsa picta, Stomoxys calcitrans, and nymphs of Ixodes ricinus, among others. Repellents exert their effects at a distance through olfactory sensitivities associated with mosquito antennae and maxillary palps. It has been reported how DEET, picaridin, IR3535, and PMD activated the odor receptor CquiOR136 of Culex quinquefasciatus, responsible for the detection and repellence …”
Section: Introductionmentioning
confidence: 99%
“…Citriodiol has also demonstrated repellent properties against Ixodes ricinus tick (Dautel et al, 2013) and land leeches of the genus Haemadipsa (Kirton, 2005). The presence of citriodiol and 1,8-cineole in the extract from Colombia might explain the differences in response of T. castaneum to these essential oils extracted from E. citriodora.…”
Section: Insecticide Activity By Contact Against Tribolium Beetlesmentioning
confidence: 97%
“…In Australia, the terrestrial leech, Haemadipsidae, was the only blood-sucking invertebrate found to be a trypanosomal carrier [8] . Leech prevention options include ‘leech socks’ (with natural repellants such as tobacco leaves), salt spray, N,N-diethyl phenylacetamide (DEPA) and N,N-diethyl m-toluamide (DEET), timur oil, and lemon-eucalyptus extract (citronyl) [6] , [9] .…”
Section: Discussionmentioning
confidence: 99%